Successful treatment with end-to-end ureteral anastomosis for ureteral avulsion caused by abdominal blunt trauma a case report - Mibu, H (Hinyokika kiyo. Acta urologica Japonica, 1998)
Avulsion of ureter without renal injury is rarely caused by blunt trauma, only 28 cases having been reported in Japan. A 33-year-old male was admitted to our hospital 1 month after blunt abdominal trauma at work. He complained of left flank pain and macroscopic hematuria. Under the suspicion of renal or ureteral injury, drip infusion urography and abdominal computerized tomography revealed an extravasation from the left upper ureter and urinoma formation in the retroperitoneal cavity. In order to reduce the inflammation, the urinoma was drained. The retrograde pyelogram revealed complete obstruction at the left upper ureter, 20 cm from the left ureteral orifice. Urinary tract reconstruction, end-to-end ureteral anastomosis, was performed under the diagnosis of left ureteral avulsion. Drip infusion urography revealed normal ureteral healing without stricture formation at 2 years after reconstruction